2022
DOI: 10.31584/jhsmr.2022904
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and COVID-19: Possible Interactions and Mechanisms in Comorbid Patients

Abstract: Beginning in December 2019 and still ongoing, coronavirus disease 2019 (COVID-19) infections have posed a public health challenge worldwide. There have been reports of diabetes mellitus (DM) as one of the most prevalent comorbidities in patients with COVID-19. Although the interactions and possible mechanisms of this association have not been fully established, the existence of DM is believed to aggravate the adverse effects of COVID-19 infection. Hence, the need for this paper. Findings from other studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 105 publications
0
1
0
Order By: Relevance
“…Cardiovascular and metabolic disease patients may have a greater risk of clinical deterioration in COVID-19. In an earlier study, the severe COVID-19 group showed a higher incidence of pre-existing hypertension, cardio-cerebrovascular disease, and diabetes compared with the non-severe group of about two-fold, three-fold, and two-fold, respectively 21,22 . The possible underlying mechanism was suggested a being that a SARS-CoV2 attack over the endothelium aggravated chronic systemic endothelial dysfunction in patients with cardiovascular and metabolic diseases 23 .…”
Section: Discussionmentioning
confidence: 86%
“…Cardiovascular and metabolic disease patients may have a greater risk of clinical deterioration in COVID-19. In an earlier study, the severe COVID-19 group showed a higher incidence of pre-existing hypertension, cardio-cerebrovascular disease, and diabetes compared with the non-severe group of about two-fold, three-fold, and two-fold, respectively 21,22 . The possible underlying mechanism was suggested a being that a SARS-CoV2 attack over the endothelium aggravated chronic systemic endothelial dysfunction in patients with cardiovascular and metabolic diseases 23 .…”
Section: Discussionmentioning
confidence: 86%